THE ADVENTURES OF TOM SAWYER - Twain. Mark (Newbury, Berkshire : CCS Books, 2019)
Tom Sawyer and Huckleberry Finn witness a murder, run away from home, and find a treasure in nineteenth-century Missouri.
Primary.
Keywords: Sawyer, Tom -- (Fictitious character) -- Comic books, strips, etc; Runaway children -- Comic books, strips, etc; Children's stories -- Comic books, strips, etc; Graphic novels; Comics adaptations